Assessment of the Quality, Content, and Reliability of YouTube Videos on Automated External Defibrillator Use: A Cross-Sectional Study - Mohamed Fayed; Zeinab Mostafa; Fouzia Ahmed; Kaleem Basharat; Mohammed Adly; Serdar Karakullukçu; Sinan Paslı; Salah Idris; Esam Jerjawi; Keebat Khan (Emergency Medicine International)
Conclusion: The main findings of our study were that most of the videos were uploaded by health institutions and were shorter. Video scores did not differ according to the level of loyalty of the mannequins used and the uploading source.